ANALYSIS OF SAVE AND LOAN INFORMATION SYSTEM AT COOPERATIVE KARYA BAKTI PEMATANG SIANTAR - Victor Pakpahan; Azwar Aliansyah Saragih (INFOKUM, 2020)
A savings and loan cooperative is a cooperative whose business activities are to collect and distribute funds to its members at low interest rates. This cooperative is also known as a credit cooperative where the management is carried out independently and democratically, and the members join voluntarily. There is also a mention that savings and loan cooperatives are non-bank financial institutions that have a business of accepting deposits from their members and providing loans to their members. The savings and loan information system at the Karya Bakti Pematang Siantar cooperative already exists and is already running in the data processing process, the application used is Visual Basic 6.0 as a programming language and MySQL as a database. Here the author will analyze the system and will build the system. The application used to build the system is XAMPP and the database uses MySQL. By analyzing existing information systems the author can find out whether the system that is running is good or not, and the author will build the system so that the system can run properly and efficiently.